Descripción de las características de la accidentalidad en Ecopetrol Gerencia Complejo Barrancabermeja en el periodo de 1995 a 1997 (1998)
ABSTRACT: Wirh the purpose of knowing the real problem of the accident in the Gerencia Complejo Barrancabermeja of the Colombian Company of Petroleums, Ecopetrol, that allowed to strengthen the preventive strategies in an integral way, was carried out a descriptive study of the main characteristics of the accident inside of and outside of the work in this company among 1995 at 1997. Diverse analytic categories were considered in the analysis whose results showed the little variation in the accident indexes (frequency and severity) in the three years of study, in spite of the implementation of different actions and programs for the control of the accidents. Likewise, critical areas were identified in front of the accidents where the preventive actions become necessary in an inmediate way. The ocular lesions were the places more frequently involved in the accidents happened in the period of the study and the identified occupations as critics they were the electrician, the pailero and the welder. It was opposing a situation criticizes in front of the accidents with the temporary workers contrary to the workers with work contract to indefinite term. The intend in consequence a series of recomendations that you/they will allow to improve the work conditions and the workers' health in an integral way, guaranteeing an effective impact on the accidents in this company.